Sex-Specific Associations of MIR137 Polymorphisms With Schizophrenia in a Han Chinese Cohort - Yin, Jingwen; Luo, Xudong; Peng, Qian; Xiong, Susu; Lv, Dong; Dai, Zhun; Fu, Jiawu; Wang, Ying; Wei, Yaxue; Liang, Chunmei; Xu, Xusan; Zhang, Dandan; et al. (Frontiers in Genetics, 2021)
Objective: To investigate the effects of microRNA-137 (miR-137) polymorphisms (rs1198588 and rs2660304) on the risk of schizophrenia in a Chinese Han population. Methods: Schizophrenia was diagnosed according to the DSM-V. Clinical symptoms and cognitive function were assessed with the Positive and Negative Symptom Scale (PANSS) and Brief Assessment of Cognition in Schizophrenia (BACS), respectively. The polymorphisms were genotyped by improved multiplex ligation detection reaction (iMLDR) technology in 1116 patients with schizophrenia and 1039 healthy controls. Results: Significant associations were found between schizophrenia and miR-137 in the distributions of genotypes (P = 0.037 for rs1198588; P = 0.037 for rs2660304, FDR corrected) and alleles (P =0.043 for rs1198588; P = 0.043 for rs2660304, FDR corrected) of 2 SNPs. When the population was stratified by sex, we found female-specific associations between miR-137 and schizophrenia in terms of genotype and allele distributions of rs1198588 (χ2 =4.41, P=0.036 and χ2=4.86, P=0.027, respectively, FDR corrected) and rs2660304 (χ2=4.74, P=0.036 and χ2=4.80, P=0.029, respectively, FDR corrected) SNPs. Analysis of the miR-137 haplotype rs1198588-rs2660304 showed a significant association with schizophrenia in haplotype T-T (χ2 = 4.60, P =0.032, OR =1.32, 95% CI (1.02-1.70)). Then, significant female-specific associations were found with the haplotypes T-T and G-A (χ2 = 4.92, P =0.027, OR =1.62, 95% CI (1.05-2.50); χ2 = 4.42, P = 0.035, OR = 0.62, 95% CI (0.39-0.97), respectively). When the TT genotype of rs1198588 was compared to the GT+GG genotype, clinical characteristics analysis also showed a female-specific association in category instances (t=2.76, P=0.042, FDR corrected). Conclusion: The polymorphisms within the miR-137 gene are associated with susceptibility to schizophrenia, and a female-specific association of miR-137 with schizophrenia was reported.